Using 13N2 and PET to track in vivo nitrogen gas kinetics during normobaric conditions - Ashworth, Edward T.; Ogawa, Ryotaro; Vera, David R.; Lindholm, Peter (Frontiers in Physiology, 2025)
IntroductionDecompression sickness (DCS) during extravehicular activity in space or after diving is caused by gaseous nitrogen. The pathophysiology is still not fully understood, as mechanisms of dissolved gas uptake and bubble development are challenging to study. We aimed to develop a new method using nitrogen-13 (13N2) gas in vivo using positron emission tomography (PET) under normobaric pressure.MethodsA single anesthetized and ventilated Sprague Dawley rat lay supine inside a PET scanner for 30 min. The rat breathed oxygen for the first 2 min, then 13N2 gas mixed with oxygen for 20 min, then oxygen alone for the final 8 min. Following the scan, a mixed blood sample was taken from the heart, while the brain, liver, femur and thigh muscle were removed to determine organ radioactivity using a gamma counter.ResultsThe signal intensity in the PET scanner increased from baseline (0.03) to 2–12 min (0.68 ± 0.31), and 12–22 min (0.88 ± 0.06), before reducing slightly from 22 to 30 min (0.61 ± 0.04). All organs had radioactivity when measured in the gamma counter. We confirmed that the gas decayed radioactivity in expectance with the half-life of 13N2 (R2 = 0.9324), and that the spectroscopy peaked just over 500 keV, suggesting no additional isotopes were present.DiscussionThis study successfully demonstrated a quantitative method of tracking nitrogen gas through the body both in vivo using PET and ex vivo using a gamma counter.